Combined intravoxel incoherent motion and diffusion tensor imaging of renal diffusion and flow anisotropy. Issue 4 (21st April 2014) - Notohamiprodjo, Mike; Chandarana, Hersh; Mikheev, Artem; Rusinek, Henry; Grinstead, John; Feiweier, Thorsten; Raya, José G.; Lee, Vivian S.; Sigmund, Eric E.
Abstract : Purpose: We used a combined intravoxel incoherent motion–diffusion tensor imaging (IVIM‐DTI) methodology to distinguish structural from flow effects on renal diffusion anisotropy. Methods: Eight volunteers were examined with IVIM‐DTI at 3T with 20 diffusion directions and 10 b ‐values. Mean diffusivity (MD) and fractional anisotropy (FA) from DTI analysis were calculated for low ( b ≤ 200 s/mm 2 ), high ( b > 200 s/mm 2 ), and full b ‐value ranges. IVIM‐parameters perfusion‐fraction fP, pseudo‐diffusivity Dp, and tissue‐diffusivity Dt were first calculated independently on a voxelwise basis for all directions. After estimating a fixed isotropic fp from these data, global anisotropies of Dt and Dp in the cortex and medulla were determined in a constrained cylindrical description and visualized using polar plots and cosine scatterplots. Results: For all b ‐value ranges, medullary FA was significantly higher than that of the cortex. The corticomedullary difference was smaller for the high b ‐value range. Significantly higher fp and Dt were determined for the cortex and showed a significantly higher directional variance in the medulla. Polar plot analysis displayed nearly isotropic Dp and Dt in the cortex and anisotropy in the medulla. Conclusion: Both flow and microstructure apparently contribute to the medullary diffusion anisotropy. The described novel method may be useful in separating decreased tubular flow from irreversible structural tubular damage, for example, in diabetic nephropathy or during allograft rejection.Magn Reson Med 73:1526–1532, 2015. © 2014 Wiley Periodicals, Inc.